IMPLEMENTASI LEAN SIX SIGMA, MULTI ATRIBUT FAILURE MODE ANALYSIS, DAN FUZZY ANALITIC HIERARCHY PROCESS UNTUK MENGIDENTIFIKASI PENYEBAB POTENTIAL DEFECT PADA PRODUK PARTICLE BOARD - Mustakim, Mustakim; Soeparman, Soedjito; Surachman, Surachman (JEMIS (Journal of Engineering & Management in Industrial System), 2015)
Abstract One of increasing in product can be undertaken by working up the activity that it has value added for each their products and getting rid of various kind of extravagances, or it is called by Lean Thinking. In this research, the writer uses An approach to integrate the concept of Lean Six Sigma, Multi Attribute Failure Mode Analysis and Fuzzy AHP is to identify the cause of Potential Defect to reduce the defect product on the particle board product.  From the results of the regressive analysis, it performs that the independent variable  (Potential Defect) takes an important role to the mount of production that it can be stared to the Defect which has a high quality. Furthermore, the defect is called as blister. So, in this research, the writer is interested to study the defect blister. The causative element of blister itself consists of  some elements. They are machine factor, human, and material elements. There are 17 elements that found in it, according to the result of analysis in using the concept of approachment Lean, Six Sigma, Multi Attribute Failure Mode Analysis and FUZZY AHP is useful to identify (the element M) that it has over size. So that, it is able to cause the failure  of potential defect with a good quality that it is as big as 0,087. So, it can be stated that the conformation of standard to the output chipper machine and do a compliance to the Gap knife ring to the Flaker machine, so that it is able to reduce the potential defect to the tune of 39,5%.